2020
DOI: 10.1037/fam0000602
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic study of parental emotion socialization: Unique contributions of fathers.

Abstract: The socialization of emotion in preschool-aged children is an important developmental task, which is associated with a number of socioemotional outcomes. This study examined the contribution of both fathers' and mothers' emotion coaching to their 3-to 4-year-old children's emotion socialization. Two time points of data were collected for 69 families. We employed a time sampling observational method to capture the emotion socialization process in the naturalistic home environment. Fathers' and mothers' emotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…This was true in relation to direct effects of supportive/unsupportive parenting on social skills, direct effects of supportive/unsupportive parenting on negative reactivity and indirect effects of supportive/unsupportive parenting on social skills. These findings added evidence to recent research valuing the fathers' role in emotional socialization process (e.g., Cherry & Gerstein, 2021;Gerhardt et al, 2020;Maia & Pereira, 2021;Yaremych & Volling, 2018). In the present study, fathers made unique contributions to their children's socio-emotional development.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This was true in relation to direct effects of supportive/unsupportive parenting on social skills, direct effects of supportive/unsupportive parenting on negative reactivity and indirect effects of supportive/unsupportive parenting on social skills. These findings added evidence to recent research valuing the fathers' role in emotional socialization process (e.g., Cherry & Gerstein, 2021;Gerhardt et al, 2020;Maia & Pereira, 2021;Yaremych & Volling, 2018). In the present study, fathers made unique contributions to their children's socio-emotional development.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, fathers made unique contributions to their children's socio-emotional development. Gender is an important issue in approaching how children learn about emotions, as men and women are socialized to express vs. inhibit/suppress emotions according to gendered roles defined by cultural norms that vary across communities and contexts (Gerhardt et al, 2020). The present study proved that mothers and fathers' emotion socialization practices may be differently linked to child's social outcomes.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Moreover, future research would also benefit from examining influences from ES to children within mother–father–child triadic interaction, as coparent ES ( Thomassin et al, 2017 ) or fathers’ observed ES ( Gerhardt et al, 2020 ) may be critical factors in children’s emotion regulation, mental health, and emotion expression. Finally, future longitudinal studies could highlight the individual and familial mechanisms that contribute to this topic.…”
Section: Implications Limitations and Future Workmentioning
confidence: 99%
“…Another limitation is that this model pertains to the transmission of emotion dysregulation amongst mothers with a history of child maltreatment. More research is beginning to examine the unique influence of fathers in the process of ES (e.g., Gerhardt et al, 2020) and despite widespread recognition that ES occurs within the family system (Morris et al, 2007), there is a paucity of literature on how mothers and fathers socialize children's development in an interactive way (Poon et al, 2017). A study by McElwain and colleagues (2007) found that when one parent reported low levels of supportive ES, greater support by the other parent was related to higher levels of emotional understanding in children.…”
Section: Limitationsmentioning
confidence: 99%